Pengaruh Pengawasan Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Direktorat Bina Kelembagaan Pelatihan Vokasi Kementerian Ketenagakerjaan - Hamzah, Muhammad; Lahat, Mohammad Amas; Utama, Dani Chandra (CV Warnak Johanna Nusantara, 2025)
Employee performance is an important factor in achieving organizational goals, which is influenced by the effectiveness of supervision and the level of work discipline. This study aims to examine the influence of supervision and work discipline on the performance of employees of the Directorate of Vocational Training Institutional Development of the Ministry of Manpower, both partially and simultaneously. The research method uses a quantitative approach with a survey method, involving 61 respondents who filled out a questionnaire. Data were analyzed using multiple linear regression with the help of SPSS version 26. The results showed that the supervision variable had a partial significant effect on employee performance, with a tcal value of 6.142 > a table of 1.671 and a significance of 0.000 < 0.05, so the first hypothesis (H1) was accepted. The work discipline variable also had a partial significant effect on employee performance, with a tcal value of 4.488 > a ttable of 1.671 and a significance of 0.000 < 0.05, so that the second hypothesis (H2) was accepted. Simultaneously, supervision and work discipline had a significant effect on employee performance, with a calculation value of 75.132 > a factor of 3.15 and a significance of 0.000 < 0.05, so that the third hypothesis (H3) was accepted. The R² value of 0.722 indicates that supervision and work discipline are able to explain 72.2% of the variation in employee performance, while the remaining 27.8% is influenced by other factors outside of this study.